PEMANFAATAN DATA PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK IDENTIFIKASI POTENSI BANJIR GENANGAN (Studi kasus sebagian Kota Yogyakarta) - , ROBIATUL UDKHIYAH, Drs. Sudaryatno, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
arta City. The potential of flood inundation is assumed as an area with drainage discharge capacity is smaller than the magnitude of the existing debit calculated by the method of rational design. Calculation of debit using rational method is influenced by several parameters which most data obtained from remote sensing data extraction. Its parameter are catchment area, runoff coefficient values, and value of rain intensity. Determination of Catchment area (DTA) based on Digital Elevation Model data (DEM) interpolation results of Lidar. Runoff coeffient value determined based on the type of land use classification according to the Georgia Stormwater Management Manual (2001), the classification obtained from the Quickbird imagery of visual interpretation and classification of slopes from the data DEM. Rain intensity values obtained from the data using the formula Mononobe of the rainfall data from the 2002-2012 daily made by Gumbel distribution based on maximum daily precipitation data. Debit result from rational methods compared with the discharge drainage capacity of the channel, the debit design from rational methods which exceed the capacity of drainage indicates a potential area of flood. The distribution potesial indundation will be classified according to (slope, runoff coefficient value, and value of debit axceed). The model results showed a similarity between the distribution of flood inundation location models with the reality in the field. Location of Flood inundation distributed around the Colombo Road, Terban, Kaliurang road, and Banteng raya, Catur Tunggal village. Keywords :flood inundation, remote sensing, and GIS